319 Validation of the Insomnia Severity Index Short-Form for Identifying Insomnia Disorder in Young Adult Cancer Survivors. (3rd May 2021) - Chevalier, Lydia; Michaud, Alexis; Zhou, Eric; Chang, Grace; Recklitis, Christopher
Abstract: Introduction: Insomnia is a common and impairing late effect experienced by many young adult cancer survivors (YACS). Although routine evaluation of sleep disorders in cancer survivors is recommended, lack of consensus on appropriate screening measures contributes to under-identification and under-treatment of these disorders in YACS. As screening measures are ideally as brief as possible while maintaining validity, we sought to validate the recently published three-item Insomnia Severity Index Short-Form (ISI-SF) in YACS. Methods: 250 YACS completed the ISI and the Structured Clinical Interview for the DSM-5 (SCID-5). The ISI-SF was created by summing three ISI items: distress (item #6), interference (item #7), and satisfaction (item #4). In receiver operating characteristic (ROC) analyses, area under the curve (AUC) was calculated to compare discrimination on the ISI-SF to two criteria: the full-scale ISI using a cutoff of ≥8 recently validated in this sample, and the SCID-5 insomnia module. Consistent with previous research, we specified a priori that a cut-off score on the ISI-SF with sensitivity ≥.85 and specificity ≥.75 would be acceptable. Results: The ISI-SF had excellent discrimination when compared to the full-scale ISI (AUC = .97) and a cut-off score of ≥4 met criteria with a sensitivity of 97% and specificity of 86%. The ISI-SF had good discrimination when compared to the SCID-5 (AUC = .88), but none of the cut-off scores met a priori criteria for sensitivity and specificity. A cut-off score of ≥4 came closest with a sensitivity of 94% and specificity of 70%. Conclusion: Although the ISI-SF did not meet sensitivity and specificity criteria for a stand-alone screening measure when compared to a diagnostic interview, it demonstrated utility as the first step in a two-step screening procedure. Specifically, the high sensitivity of the ≥4 ISI-F cut-off score is well-suited to accurately screening out YACS who do not need insomnia services; as a second screen, the SCID-5 insomnia module could be administered only to those elevated on the ISI-SF in order to identify false positives cases before making referrals for insomnia specialists. Support (if any): National Cancer Institute (1R21CA223832), Swim Across America